MENGURAI PERMASALAHAN SISTEM PEMILU DI INDONESIA DAN DAMPAKNYA TERHADAP DEMOKRASI - Barus, Tirta Yasa Agung; Adwiyah, Rabiatul; Lubis, Khodijah May Nuri; Rahma, Suci Nur; Faturrahman, M.Nadhif (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
General elections in Indonesia are an important mechanism in the democratic process that aims to elect people's representatives and government leaders. However, the electoral system in Indonesia faces various problems that can threaten the quality of democracy. These problems include the practice of money politics, vote manipulation, and lack of transparency in the election process. In addition, the existence of political intervention and bureaucracy that are not neutral are also serious challenges. The impact of these problems on democracy is very significant, including declining public trust in democratic institutions, weakening public political participation, and hampering the process of forming an accountable and responsive government. Therefore, a comprehensive electoral system reform is needed to strengthen democracy in Indonesia.